Hair follicle differentiation‐specific keratin expression in human basal cell carcinoma. (1st June 2020) - Morgan, H. J.; Benketah, A.; Olivero, C.; Rees, E.; Ziaj, S.; Mukhtar, A.; Lanfredini, S.; Patel, G. K.
Summary: Background: Identification of human basal cell carcinoma (BCC) cancer stem cells and cellular hierarchy inherently implies the presence of differentiation. By conventional histological analysis, BCC demonstrates tumour nodules that appear relatively homogeneous. Aim: As BCCs arise from hair follicle (HF) keratinocytes, we sought to define the pattern of HF differentiation. Methods: BCC, squamous cell carcinoma (SCC) and normal skin tissues were analysed using a microarray chip. The expression of individual keratins, regulatory pathways and proliferative states were analysed using reverse transcription‐PCR and immunofluorescence microscopy. Results: Microarray analysis of BCC, SCC and normal hair‐bearing skin revealed that BCCs express a wide range of HF genes, including HF‐ specific keratins. BCC demonstrated outer ( KRT5, KRT514, KRT516, KRT517 and KRT519 ) and inner ( KRT25, KRT27, KRT28, KRT32, KRT35, KRT71, KRT75 and KRT85 ) root sheath differentiation, but not hair shaft differentiation. As in the HF, differentiation‐specific keratins in BCC keratinocytes correlated with a reduced proliferative index and regulatory pathway activation despite the oncogenic drive towards tumour growth. Our findings show the close correlation between HF and BCC keratinocyte differentiation. Conclusion: This work has defined the differentiation pattern within BCCs, enabling development of targeted therapies that promote differentiation and result in BCC cancer stem cell exhaustion.